Combination of agomelatine and bupropion for treatment‐resistant depression: results from a chart review study including a matched control group. Issue 4 (19th February 2015) - Sühs, Kurt‐Wolfram; Correll, Christoph; Eberlein, Christian K.; Pul, Refik; Frieling, Helge; Bleich, Stefan; Kahl, Kai G.
Abstract Introduction Although a growing selection of antidepressants is available, a significant number of patients do not reach clinical remission, despite multiple trials. Data concerning the efficacy and safety of combination therapies with newer antidepressants are limited. Methods Fifteen inpatients with treatment‐resistant depression (TRD), defined as Beck Depression Inventory‐2 (BDI‐2) scores >14 despite treatment with adequate doses of ≥1 antidepressant classes for ≥6 weeks, were treated with agomelatine plus bupropion for ≥6 weeks, and compared to 15 patients on antidepressant monotherapy with TRD matched on age, sex, and TRD stage based on retrospective chart review. The primary outcome was change in BDI‐2 scores. Secondary outcomes included treatment response (BDI‐2 score decrease by ≥50%), remission (BDI‐2 score <13), routinely measured cardiometabolic parameters and adverse effects. Results After a mean of 6 ± 1 weeks, BDI‐2 scores decreased by 20.3 ± 5.6 points in the combination group compared to 12.5 ± 15.1 points in the monotherapy group (P = 0.073; Cohen's d = 0.7). Altogether, 73.3% in the combination group responded compared to 53.3% on monotherapy (P = 0.27). About 60.0% on combination therapy reached remission compared to 40% on monotherapy (P = 0.28), a difference equivalent to a number‐needed‐to‐treat = 4. Treatment response was independent of the degree of TRD (P = 0.27). Bupropion‐agomelatine cotreatment was well tolerated and laboratory adverse effect parameters were not altered. Conclusion Despite the small sample and uncontrolled study design, the good remission rate in TRD patients receiving agomelatine plus bupropion, particularly in comparison to the monotherapy group, indicates that this combination treatment should be explored further as a potentially promising strategy for patients with TRD.